Gurewich ole controls for visual basic 4 with cd. - Gurewich, Ori.; Gurewich, Nathan (Indianapolis Sams Publishing, 1995)
Through step by step tutorials, this guides teaches how an actual professional OCX custom control is implemented by first developing the prototype of the OCX, and then developing the control.